Factors Associated With Cancer Incidence and With All-Cause Mortality After Cancer Diagnosis Among Human Immunodeficiency Virus-Infected Persons During the Combination Antiretroviral Therapy Era. (27th May 2014) - Patel, Pragna; Armon, Carl; Chmiel, Joan S.; Brooks, John T.; Buchacz, Kate; Wood, Kathy; Novak, Richard M.
Abstract: Background.  Little is known about survival and factors associated with mortality after cancer diagnosis among persons infected with human immunodeficiency virus (HIV). Methods.  Using Poisson regression, we analyzed incidence rates of acquired immune deficiency syndrome (AIDS)-defining cancers (ADC), non-AIDS-defining infection-related cancers (NADCI), and non-AIDS-defining noninfection-related cancers (NADCNI) among HIV Outpatient Study participants seen at least twice from 1996–2010. All-cause mortality within each cancer category and by calendar period (1996–2000, 2001–2005, 2006–2010) were examined using Kaplan-Meier survival methods and log-rank tests. We identified risk factors for all-cause mortality using multivariable Cox proportional hazard models. Results.  Among 8350 patients, 627 were diagnosed with 664 cancers. Over the 3 time periods, the age- and sex-adjusted incidence rates for ADC and NADCNI declined (both P < .001) and for NADCI did not change ( P = .13). Five-year survival differed by cancer category (ADC, 54.5%; NADCI, 65.8%; NADCNI, 65.9%; P = .018), as did median CD4 cell count (107, 241, and 420 cells/mm 3 ; P < .001) and median log10 viral load (4.1, 2.3, and 2.0 copies/mL; P < .001) at cancer diagnosis, respectively. Factors independently associated with increased mortality for ADC were lower nadir CD4 cell count (hazard ratio [HR] = 3.02; 95% confidence interval [CI], 1.39–6.59) and detectable viral load (≥400 copies/mL; HR = 1.72 [95% CI, 1.01–2.94]) and for NADCNI, age (HR = 1.50 [95% CI, 1.16–1.94]), non-Hispanic black race (HR = 1.92 [95% CI, 1.15–3.24]), lower nadir CD4 cell count (HR = 1.77 [95% CI, 1.07–2.94]), detectable viral load (HR = 1.96 [95% CI, 1.18–3.24]), and current or prior tobacco use (HR = 3.18 [95% CI, 1.77–5.74]). Conclusions.  Since 1996, ADC and NADCNI incidence rates have declined. Survival after cancer diagnosis has increased with concomitant increases in CD4 cell count in recent years. Advances in HIV therapy, including early initiation of combination antiretroviral therapy, may help reduce mortality risk among HIV-infected persons with cancer.